Financial Accounting Transformation in the Digital Era: Challenges and Opportunities for the Accounting Profession - Ummu Kalsum; Tenriwaru Tenriwaru; Edy Susanto (Penerbit Goodwood, 2026)
Purpose: This study examines how digital transformation reshapes financial accounting practices and influences the role of the accounting profession in implementing Standar Akuntansi Keuangan (SAK) in the digital era. Research Methodology: This study employs an exploratory qualitative approach using semi-structured interviews with eight informants, consisting of accounting educators and external auditors in Makassar, Indonesia. Participants were selected through purposive sampling based on their experience with digital accounting systems. Data were analyzed using thematic analysis to identify patterns related to role changes, challenges, and opportunities in SAK implementation. Results: The findings indicate that digital transformation does not change the substantive principles of SAK but significantly alters the mechanisms through which these standards are implemented. Financial reporting processes are increasingly integrated within digital accounting systems that automate transaction recording and enable real-time financial reporting. Consequently, the role of accountants has shifted from traditional administrative record keepers to more analytical and strategic professionals responsible for evaluating accounting systems and ensuring compliance with accounting standards. Conclusions: Digital transformation reflects an institutional adaptation process in which technological change reshapes accounting practices without replacing existing regulatory frameworks. Limitations: This study is limited by its small sample size and regional focus. Contributions: This study contributes to the literature by integrating institutional theory with digital accounting transformation and explaining how regulatory, normative, and cognitive factors influence SAK implementation.